Improve the accuracy rate of link quality estimation using fuzzy logic in mobile wireless sensor networks / Huang Zhirui - Huang , Zhirui (2019)
Link quality estimation is essential for improving the performance of a routing protocol in Wireless Sensor Networks. Many methods have been proposed to increase the performance of the link quality estimation, however, most of them are not able to evaluate link quality accurately. In this study, a method that uses fuzzy logic to evaluate both hardware-based and software-based metrics is proposed to improve the accuracy rate for evaluating a link quality. This proposed method consists of three types of modules, the Fuzzifier module, the Inference module, and the Defuzzifier module. The Fuzzifier module is used to determine the degree to which input link quality metrics belong to each fuzzy set using proposed membership functions. The Inference module obtains the rule outputs based on the proposed fuzzy rules and the given inputs acquired from the Fuzzifier module. The Defuzzifier module is used to aggregate the rule outputs inferred from the Inference module. The result from the Defuzzifier module is then used to evaluate the link quality. A simulation was conducted to evaluate the accuracy rates of the proposed method and those found in the other related works. The results showed that the proposed method had a higher accuracy rate than the other related works for evaluating a link quality.